The Production of Mammary Carcinomas in Rats by 9,10-Dimethyl-1,2-Benzanthracene and its Relationship to the Oestrous Cycle - Young, Stretton (Nature Publishing Group, 1970)
Sprague-Dawley rats aged 50 days were given single oral doses of the carcinogen, DMBA. Rats receiving the carcinogen at the same stage of the oestrous cycle were grouped together and mammary tumour production was compared between these groups. When the carcinogen was given during di-oestrus the mean number of tumours per animal was significantly greater than when it was given at other stages in the oestrous cycle. There was considerable variation in total tumour yield from one batch of animals to another.